Investing psychology : the effects of behavioral finance on investment choice and bias - Richards, Tim, 1961- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
Discover how to remove behavioral bias from your investment decisions For many financial professionals and individual investors, behavioral bias is the largest single factor behind poor investment decisions. The same instincts that our brains employ to keep us alive all too often work against us in the world of finance and investments. Investing Psychology + Website explores several different types of behavioral bias, which pulls back the curtain on any illusions you have about yourself and your investing abilities. This practical investment guide explains that conventional financial wisdom is often nothing more than myth, and provides a detailed roadmap for overcoming behavioral bias.
#4: Be Skeptical.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Investments -- Psychological aspects; Finance -- Psychological aspects; Business; Finance -- Psychological aspects; Investments -- Psychological aspects; BUSINESS & ECONOMICS -- Finance; Finance -- Psychological aspects; Investments -- Psychological aspects; Electronic books